Towards Techno-human: A Brief History of Artificial Limbs and Organs - Bardakçı, Tayyibe (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: The ‘techno-human’, which is the result of combining the human body with a machine or device which we have been made familiar with through science fiction movies, is frequently perceived as a distant and futuristic concept. However, when we examine history, we realize that the techno-human is not a phenomenon unique to the future or the present, but rather has a long and significant history dating all the way back to antiquity. Objective: This study aims to detail the progression of techno-humans from antiquity to the present, by focusing on the historical development of artificial limbs and organs. Methods: In this study, a literature review ranging from the earliest examples of the human body meeting technology to today’s complex and functional artificial limb and organ technologies was conducted, and the information gathered through retrospective review of primary and secondary sources was evaluated. Results and Discussion: It is seen that people who lost their limbs as a result of amputation or disease have been using prostheses, albeit primitive, since ancient times. Today, advances in technology such as CAD/CAM and 3D printer technologies enable the production of prostheses from lighter materials and at a faster rate. Contrary to the long history of artificial limbs dating to antiquity, the development of artificial organs only began recently, during the 20th century. Artificial limbs and organs, with the use of more advanced technology, have the potential to be utilized for human enhancement in the future. Conclusion: While prostheses, implants, and complexly built artificial organs make the human body more technological and less biological, a new stage in the biography of the techno-human in which ‘enhancement’ rather than ‘treatment’ is at the forefront pushes the limits. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 249-257